STRUCTURAL OPTIMIZATION UNDER EXTREME CONDITIONS: ENGINEERING DESIGN FOR CLIMATE-INDUCED HAZARDS - Saripuddin M; Ethan Tan; Giovanni Rossi (Yayasan Adra Karima Hubbi, 2026)
Structural infrastructure worldwide faces increasing exposure to climate-induced hazards, including extreme flooding, high-intensity wind events, prolonged heat waves, and compound environmental stressors that challenge conventional engineering design standards. Growing uncertainty associated with climate change necessitates innovative approaches capable of enhancing resilience while maintaining structural efficiency and economic feasibility. This study aims to examine the effectiveness of structural optimization strategies in improving infrastructure performance under extreme environmental conditions. A quantitative engineering research design was employed using finite element modeling, climate hazard simulations, probabilistic risk assessment, and multi-objective optimization techniques. Structural systems were evaluated across multiple hazard scenarios to assess resilience, reliability, material efficiency, failure probability, and lifecycle cost performance. Results indicate that optimized structures achieved significantly higher resilience scores, improved structural reliability, reduced stress concentrations, lower failure probabilities, and greater material efficiency compared with conventional designs. Optimization-based configurations demonstrated superior adaptability to future climate scenarios and maintained operational performance under severe loading conditions. Case-study simulations further revealed substantial reductions in displacement and maintenance requirements while improving long-term infrastructure sustainability. Findings suggest that integrating climate projections with advanced optimization frameworks can substantially strengthen engineering resilience and support more effective adaptation strategies. Structural optimization therefore represents a promising pathway for developing safer, more sustainable, and climate-responsive infrastructure systems capable of addressing emerging environmental risks.